PENERAPAN MODEL PEMBELAJARAN OPEN ENDED PROBLEM UNTUK MENINGKATKAN HASIL BELAJAR SISTEM KOPLING GANDA - Raflyanto; Wiyogo; Jhonni Rentas Duling (Steam Engineering, 2019)
This study aims to determine; (1) teacher activities after applying the open ended problems learning model in class XI TBSM SMKN 1 Kurun, (2) student activities after applying the open ended problems learning model in class XI TBSM SMKN 1 Kurun, (3) student responses after applying the open ended problems learning model on the double clutch system lesson, and (4) learning outcomes of class XI TBSM SMKN 1 Kurun, after following the open ended problems learning model on the double clutch system lesson. This research is descriptive quantitative, this research took the subject of class students XI TBSM SMKN 1 Kurun chosen as the subject of research. The instrument used is a test of cognitive learning outcomes, student activity sheet, teacher activity sheet, and student response questionnaires. As well as student learning outcomes related to cognitive, affective and psychomotor aspects. The results of data analysis showed that overall student activity was carried out well. The completeness of the classically tested cognitive learning outcomes of students in 13 people (92,85%) and 1 student has not yet finished (2,94%), so classically the results of student learning using open ended problems models are said to be successful